Prostota podzimu: Josef Váchal a Bohuslav Reynek: dva extrémy české grafiky - Novák, Aleš (Lidé města, 2007)
It is not really usual to interconnected two eccentric solitaires of the Czech literary and fine arts, such as Josef Váchal and Bohuslav Reynek. They are both impossible to classify, slightly eccentric, but so much more diligent artists; this in itself might be a good reason to compare their work and primarily disposition and meaning of their work.